Tight-binding description of single-mode cavity-plasmon waveguides in the frequency and time domain - G. Gantzounis; N. Stefanou (Journal of Physics: Condensed Matter, 2008)
We report a consistent derivation of a tight-binding formalism, both in the frequency and in the time domain, for the analysis of electromagnetic energy transfer in single-mode cavity-plasmon waveguides. Moreover, we derive closed-form solutions of the relevant tight-binding equations, which describe the response of these waveguides under time-varying excitations by a localized light source. In this context, we discuss the possibility of efficient single-mode waveguiding through coupled cavity-plasmon modes in chains of spheroidal silicon nanoparticles in silver at optical frequencies.